Design and Calculation of Cable Distribution System for CDPR - Tuong, Tưởng Phước Thọ; Truong, Trương Nguyễn Luân Vũ (Journal of Technical Education Science, 2024)
This article presents the design and calculation of a cable distribution system used for large-sized cable robots. The main function of the cable distribution system is to convert the rotational motion of the motor shaft into the translational motion of the cable with constraints on position, velocity and cable tension. With a clear relationship between cable length and motor angle, the cable distribution system is designed to guarantee that cables are fully distributed and oriented. The main contributions of the research are as follows: Designing a cable distribution system with a built-in mechanism for measuring cable tension; Building cable distribution system mathematical models, incorporating the results into a mathematical model of a 6-degree-of-freedom CDPR configuration powered by 8 cables and simulating the computational results. The analysis findings suggest that the structure of the cable distribution system meets the design specifications and is suitable for developing actuators in cable robot applications that involve heavy loads and large sizes.